Libri ad Nauseam: The Critical Thinking Textbook Glut - Hamby, Benjamin (Paideusis, 2013)
Critical thinking instructors are faced with an overwhelming number of textbooks to choose from for their courses. Many of these texts do not reflect an awareness of current scholarship in critical thinking and informal logic. I argue that instructors should only adopt textbooks that reflect a sound theoretical understanding of the topic by acknowledging the central role of critical thinking dispositions, offering a more nuanced approach to the teaching of fallacies and of inference, stressing dialectic and argument revision, focusing on the analysis and evaluation of real arguments, and broadening the scope of critical thinking beyond argument analysis and evaluation. To support instructors in this regard, I critique one popular textbook now in its sixth edition that does not satisfy many of these criteria, Munson and Black (2012), and applaud one new textbook that I find does succeed on many of these fronts, Bailin and Battersby (2010).